2014
DOI: 10.1002/2014gl061120
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater dating with Atom Trap Trace Analysis of39Ar

Abstract: We report on the realization of Atom Trap Trace Analysis for39Ar and its first application to dating of groundwater samples. The presented system achieves an atmospheric39Ar count rate as high as 3.58 ± 0.10 atoms/h allowing for the determination of the39Ar concentration in less than a day. We demonstrate that the measured count rates are proportional to the39Ar concentration by intercomparison with Low‐Level Counting results and by measurements on prepared argon samples with defined concentration. For a geoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…The most recent development in this field is the introduction of an analytical method from atomic physics (Atom Trap Trace Analysis), which greatly facilitates the use of the noble gas radioisotopes 39 Ar, 81 Kr, and 85 Kr (Lu et al, 2014). This new method of groundwater dating is now increasingly being applied, making successful use of the advantageous properties of the noble gas radioisotopes (e.g., Aggarwal et al, 2015;Gerber et al, 2017;Matsumoto et al, 2018;Ritterbusch et al, 2014;Yechieli et al, 2019).…”
Section: Dating Tracersmentioning
confidence: 99%
“…The most recent development in this field is the introduction of an analytical method from atomic physics (Atom Trap Trace Analysis), which greatly facilitates the use of the noble gas radioisotopes 39 Ar, 81 Kr, and 85 Kr (Lu et al, 2014). This new method of groundwater dating is now increasingly being applied, making successful use of the advantageous properties of the noble gas radioisotopes (e.g., Aggarwal et al, 2015;Gerber et al, 2017;Matsumoto et al, 2018;Ritterbusch et al, 2014;Yechieli et al, 2019).…”
Section: Dating Tracersmentioning
confidence: 99%
“…The number of 39 Ar dating studies and measurements so far were limited due to the large sample size and analytical requirement of the well established Low-Level Counting (LLC) method (Loosli and Purtschert, 2005). However, ongoing technological development efforts, in particular the Atom Trap Trace Analysis (ATTA; e.g., Lu et al, 2014), now allow for a relatively fast 39 Ar age analysis of small sample volumes (Ritterbusch et al, 2014), and are expected to increase the number of analyses in the future. Understanding the relationship between the atmosphere-and subsurface-generated 39 Ar is thus essential in deep groundwater radiometric dating, in studies of fluid circulation in the Earth's crust, circulation pathways and residence times of ocean water masses, and in dating of deep ice cores.…”
Section: Implications For Groundwater Datingmentioning
confidence: 99%
“…The adaptation of this method to 39 Ar, which we refer to as Argon Trap Trace Analysis (ArTTA), and its application to environmental studies has been demonstrated with large groundwater [15] and recently with small ocean samples [16]. ArTTA is thus the door-opener for broad application of radio-argon dating in research fields as glaciology, that have so far been excluded, due to sample size requirements [17].…”
Section: Introductionmentioning
confidence: 99%